Development of Floating Platform for Water Quality Monitoring - Zahari N.M.; Sankar P.; Zawawi M.H.; Roslin N.T.; Aziz N.A.; Nurhikmah F.; Khamarudin M.H.F. (Springer Science and Business Media Deutschland GmbH, 2025)
The fast development of the population and high-tech industries is driving water quality control unusually more critical. In addition, recent climate change is also a major factor in this issue. Regular inspections of water and collection of samples could also contribute greatly to water distribution management. Even though the water quality parameters are measured by the senor station automatically in the water reservoir, only a small number of the station is placed in the reservoir, and the ?resolution? is not sufficient for modern applications. Thus, the major goal of this study is to design and develop a surface platform prototype for water quality monitoring. Hence, this paper proposed and developed a floating device which is well known as an unmanned surface vehicle to measure water quality parameters with several advanced sensors. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.